Kapasitas Aparatur Pemerintahan Desa Baru: Studi Kasus di Desa Takatunga I Kabupaten Ngada - Maria Fenansia Ngao; Laurensius P. Sayrani; Alfred O. Ena Mau (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the Capacity of the New Village Government Apparatus in Takatunga I Village, Ngada Regency. The method used in this research is a qualitative method with a case study approach. The theory used in this research is the theory of Apparatus Capacity according to Asrori which highlights three abilities, namely basic ability, management ability and technical ability. Informants who became research sources amounted to 12 people. The data sources used are primary data and secondary data. Data collection techniques in the research are interviews, observation, documentation and literature study. Data analysis techniques used in the research are data reduction, data presentation and conclusion drawing. The results showed that the basic skills possessed by the apparatus in Takatunga I Village were inadequate, most of the apparatus did not know the basic fundamentals of village government, their main duties and functions. In addition, Takatunga I Village does not yet have a village profile and village government organizational structure. The management skills possessed by Takatunga I village officials are still very limited; there are still complaints from the community about the services provided, because there is only one official who can operate a computer. In addition, although monitoring is limited to monitoring development, evaluation in Takatunga I Village is still limited to reporting every semester. The financial disbursement process is well done, but the accountability aspect is still less than optimal. The technical capabilities of the Takatunga I Village apparatus are quite good, despite having limited facilities and mastery of technology such as computers.